The Effect of Using Hard Landscape Material on Thermal Environment (A Case Study on Malioboro Street) - Supriyanta Supriyanta; Muhammad Ginanjar (Journal of Architectural Research and Design Studies, 2019)
One of the current issues of temperature warning that is greatly discussed is Urban Heat Island (UHI). It is a phenomenon that can affect people’s level of comfort in doing outdoor activities with respect to the rising air temperature. There are many factors that affect the occurrence of UHI. One of them is the increasing use of hard landscape materials. This research was conducted to find out how big the influence of the use of hard material of the landscape on the decrease of outdoor environment temperature. The sample selection was taken on the research site, namely Malioboro Street, Yogyakarta, through the simulation of temperature evaluation using the Envi-Met software. The landscape materials studied include brick road (red stone) / red brick, sandy soil, asphalt road, dark concrete pavement, concrete pavement gray, and dark granite pavement. Then, each object of the study was tested and compared to determine the most optimal landscape component in the thermal environment degradation. From the results of the simulation test conducted through Envi-Met software, the change of thermal condition in each material can be identified. The difference in the changes that occurred between the materials tested was not quite significant. The hard landscape material that absorbs heat the least, and thus causing the largest thermal temperatures is the brick material, while the environment with the lowest thermal conditions use sandy soil material.Keywords: Landscape elements, Thermal environment, Temperature